Profitability and investment‐based factor pricing models. (20th June 2016) - Elliot, Brendan; Docherty, Paul; Easton, Stephen; Lee, Doowon
Abstract: Ex ante predictors of stock returns must exhibit explanatory power across the feasible set of investments. But empirical results of factor pricing models that incorporate firm investment and profitability cannot explain the apparently high returns of US small stocks with very high investment levels and very low profitability. Whilst these stocks comprise only a small fraction of US data sets, this is not the case across global markets. Using a data set that is concentrated with stocks that exhibit high investment despite low profitability, we demonstrate that such factor models are limited in their explanatory power over these stocks.